The management of engineering - Bennett, F. Lawrence (New York : John Wiley and Sons, 1996)
This book is about: The engineer as manager; The engineering organization; Total quality management; The human element in engineering management; Communication in the engineering organization; ...
Keywords: Management; Engineering; Engineering management